Severe hyperkalaemia and ketoacidosis during routine treatment with an insulin pump. Issue 6492 (10th August 1985) - Knight, G; Jennings, A M; Boulton, A J; Tomlinson, S; Ward, J D
Abstract : During a feasibility study of the use of insulin pumps to treat diabetes ketoacidosis occurred at a rate of 0.14 episodes/patient/year in the first year but was lower in subsequent years. A case of cardiac arrest secondary to hyperkalaemia during ketoacidosis occurred in a patient treated with a pump. The mean (SD) serum potassium concentration on presentation to hospital with ketoacidosis was significantly higher in patients treated with a pump (5.7 (1.1) mmol(mEq)/l) than those treated with conventional injections of insulin (4.9(0.9) mmol/l; p less than 0.01). The high rate of ketoacidosis and raised serum potassium concentrations during treatment with the pump creates doubt about the use of this treatment as an alternative regimen for large numbers of patients in a busy diabetic clinic.